PENGEMBANGAN SISTEM INFORMASI ONLINE MENGGUNAKAN METODE WEB ENGINEERING - Ependi, Usman (Universitas Bina Darma, 2013)
Information is a thing that is needed, so the way to deliver information to influence someone to get information. Informatics Engineering Program Bina Darma University to convey information to students not yet have the most effective media, so that information such as exam schedules or thesis proposal, or thesis proposal examination scores, courses, syllabus / SAP, articles, free software, proposal / thesis , suggestions and questions, announcements, news regarding academic and other matters Information Engineering Program Bina Darma University can not be delivered quickly to the students or the community at large. So one way to convey information through or use Oneline Information System. Submission of information through the Online Information System can be accessed anytime and anywhere. The information system also has a method in its development phase in which one of them is web engineering, where meotde is used in the development of this information system engineering informatics. Keyword: information, System, Online, Informatics Engineering Program